PEMBELAJARAN MENYIMAK LANJUTAN DI SEKOLAH DASAR - Qalbi, Nur; Hamzah, Rahma Ashari; Imelda, Imelda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Listening is one of the fundamental language skills that significantly influences students' language comprehension and communication abilities. In elementary school, advanced listening instruction is often overlooked, resulting in students"™ low ability to analyze, interpret, and respond to spoken texts critically. This study aims to explore the implementation of advanced listening learning in elementary schools and its impact on students"™ listening comprehension skills. A qualitative descriptive method was used, involving classroom observations, interviews with teachers, and document analysis. The data were analyzed through data reduction, data display, and conclusion drawing. The results show that the implementation of advanced listening learning is still limited and tends to focus only on basic listening skills, such as identifying main ideas or keywords. Teachers rarely use varied and interactive listening strategies, such as note-taking, predicting content, or responding to audio-visual materials. Furthermore, it was found that students often face difficulties in retaining detailed information and making inferences from what they listen to. The study concludes that there is an urgent need for more structured and engaging listening learning approaches that go beyond the basic level, integrating technology and student-centered strategies to improve comprehension and critical thinking. This research is expected to be a reference for developing more effective listening instruction in elementary education.